The holiday - Meyers, Nancy; Block, Bruce A.; Diaz, Cameron; Winslet, Kate.; Law, Jude, 1972- ([United States] : Universal Pictures/Columbia Pictures, 2006)
Meet Iris and Amanda, two women who couldn't be more different. One lives in a cosy English cottage, the other in a swanky Hollywood estate, but both are alike in their mutual bad luck with men. In desperate need of an escape, they meet online and impulsively switch homes. Both find the last thing either wants or expects - a new romance - and discover that a change of address really can change your life.
Director, Nancy Meyers ; producer, Bruce A. Block.
Cameron Diaz, Kate Winslet, Jude Law, Jack Black.
Rated M: Suitable for mature audiences 16 years and over. Contains offensive language and sexual references.
DVD ; Region 2,4,5, PAL.
In English with sub-titles in English, Danish, Finnish, Norwegian, Arabic, Dutch, Icelandic, Swedish. Closed-captioned in English for the hearing impaired.
105447
Keywords: Feature films; Romance films; Christmas Films; Comedy films